Effect of doping metal ions on microstructural evolution and dielectric behaviors of CaCu3Ti4O12 ceramics synthesized by semi-wet route - Pandey S.; Kumar V.; Sharma V.K.; Mandal K.D. (My University, 2025)
In this paper, we have synthesized CaCu3Ti3.5X0.5O12 (X = Mn, Nb, and W) on Ti-sites. We focus particularly on the effect of different doped metal ion and the sintering temperature on grain growth, microstructure and dielectric function of metal ion-doped CaCu3Ti4O12. The metal ion-doped CaCu3T4-XMnxO12 was prepared successfully through the semi-wet route. The Phase of CCTXO (Mn, Nb, and W) were confirmed by XRD which containing major phases as CaCu3Ti4O12 along with minor phases as TiO2 sintered at a different temperature depending on the doped metal ion. The dielectric constant measured at different temperatures in the range of 100 Hz −1 MHz frequency. The particle size and grain size (microstructure) studied by the TEM as well as SEM techniques. The dopant metal ion oxidation state was confirmed by XPS spectroscopy. © 2020 Elsevier B.V.